Comparison of Security Signing Data Authentication Integrity in Combination of Digest And AES Message Algorithm - Rasna Rasna; Irjii Matdoan; Sitti Alam (International Journal of Informatics and Information Systems, 2021)
Online information systems with the Single Sign-On (SSO) model are currently widely used by many companies. Single Sign-On (SSO) is an independent authentication model. This system runs on the Hypertext Transfer Protocol (HTTP) protocol. Sending data or information without security is at risk of eavesdropping on information by the authorities. This study aims to compare the combination of Message-Digest and Advanced Encryption Standard (AES) algorithms to improve data security by modifying dynamic keys. The test results show that in each execution the user name and password with the MD5 algorithm are always the same while in the AES algorithm the results are always different so it is safe from replay attacks. So that the Advanced Encryption Standard (AES) algorithm can secure data through the Single-Sign-On authentication process with high-security accuracy.